2021
DOI: 10.1177/10781552211043836
|View full text |Cite
|
Sign up to set email alerts
|

Lesson learned from the pandemic: Isolation and hygiene measures for COVID-19 could reduce the nosocomial infection rates in oncology wards

Abstract: Introduction It was previously demonstrated that seasonal influenza incidence was significantly decreased during the COVID-19 pandemic, possibly due to respiratory and hygiene precautions. From this point, we hypothesized that the COVID-19 precautions could lead to a decrease in nosocomial infection rates in oncology inpatient wards. Methods We evaluated the nosocomial infection rates in an inpatient palliative oncology ward in the first 3 months of the COVID-19 pandemic in our country and compared this rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Studies described nurse-led quality initiatives in the form of nurse-led toolkits 52,53 , a multidisciplinary stakeholder team 53 , and a training model 54 . One study also described using respiratory hygiene procedures like those used during influenza epidemics to reduce COVID-19 transmission 49 . Bundling technology together with education was evaluated to reduce central line-associated blood stream infections and catheter-associated urinary tract infections 55 .…”
Section: Heath Care-associated Infections (Hai)mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies described nurse-led quality initiatives in the form of nurse-led toolkits 52,53 , a multidisciplinary stakeholder team 53 , and a training model 54 . One study also described using respiratory hygiene procedures like those used during influenza epidemics to reduce COVID-19 transmission 49 . Bundling technology together with education was evaluated to reduce central line-associated blood stream infections and catheter-associated urinary tract infections 55 .…”
Section: Heath Care-associated Infections (Hai)mentioning
confidence: 99%
“…There were 42 studies that assessed the use of various modified procedures across all safety domains. Many of these studies also described other intervention themes, such as the use of modified safety checklists 35 , care pathways 17,25,42 , environmental modification 64 , and changes in procedures and hygiene practices 49,51 . One study evaluated management of pharmaceutical interventions and added pharmacists to the team to reduce medication errors 65 .…”
Section: Modified Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Another meta-analysis of 23 studies yielded inconclusive results [15], but there have been reports of increased antibiotic resistance during the COVID-19 pandemic [16,17]. In contrast, several studies have reported reductions in antibiotic-resistance prevalence during the pandemic [18][19][20]. The uncertainties regarding COVID-19 diagnosis and concerns over bacterial co-infections or secondary infections likely underpinned substantial but inappropriate prescription of antibiotics [15].…”
Section: Introductionmentioning
confidence: 99%